Fenomena Perubahan Preferensi Pembelian Mahasiswa Universitas Negeri Semarang (UNNES) Dari Offline Ke Online: Studi Kasus Pada Warung Makan Prasojo - Femas Dwi Nurcahyanto; Brian Adi Sugara; Rauly Sijabat (JURNAL ILMIAH NUSANTARA, 2026)
The development of digital technology has fundamentally transformed consumer behavior, particularly among university students, in shifting food purchasing methods from offline to online. This phenomenon is also observed at Warung Makan Prasojo, located in the Gunung Pati area of Semarang, which has long been a favorite dining spot for students of Universitas Negeri Semarang (UNNES). This study aims to understand how UNNES students perceive the shift in purchasing preferences from offline to online and its implications for the business sustainability of Warung Makan Prasojo. This research employs a qualitative approach with a case study method. Data were collected through in-depth interviews with UNNES students who have experience in both offline and online food purchases at Warung Makan Prasojo. Informants were selected using a purposive sampling technique. Data analysis followed the Miles and Huberman model, encompassing data reduction, data display, and conclusion drawing. The study utilized the Theory of Planned Behavior (TPB) as the theoretical framework. The results indicate that students tend to choose online purchasing because it is considered more practical, time-efficient, and supported by delivery service application promotions. Furthermore, social environmental influences, ease of technological access, and uncomfortable physical dining conditions further drive the shift in purchasing preferences toward online platforms.